Capacity utilisation, constraints and price adjustments under the Microscope - Sarah M. Lein; Eva Köberl (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper analyses the interplay of capacity utilisation, capacity constraints, demand constraints and price adjustments, employing a unique firm-level data set for Swiss manufacturing firms. Theoretically, capacity constraints limit the ability of firms to expand production in the short run and lead to increases in prices. Our results show that, on the one hand, price increases are more likely during periods when firms are faced with capacity constraints. Constraints due to the shortage of labour, in particular, lead to price increases. On the other hand, we also find evidence that firms are not reluctant to reduce prices in response to demand constraints. At the macro level, the implied capacity-utilisation Phillips curve has a convex shape during periods of excess demand and a concave shape during periods of excess supply. Our results are robust to the inclusion of proxies for changes in costs and the competitive position of firms.
Keywords: E31; E32; E52; 330; price setting; capacity utilisation; capacity constraints; demand constraints; non-linear Phillips curve; Switzerland; Kapazitätsauslastung; Betriebliche Preispolitik; Produktionskapazität; Nachfrage; Phillips-Kurve; Verarbeitendes Gewerbe; Schweiz